Win, lose, or draw in the fog of civil war. (September 2018) - Greig, J Michael; Mason, T David; Hamner, Jesse
Civil war outcome studies have used expected utility logic to identify factors that affect actors' estimates of the probability of victory, the payoffs from victory vs defeat, and the accumulated costs of fighting until victory is achieved. Tests have used static measures of national attributes and war characteristics, measured prior to the war or at its end. We use UCDP Georeferenced Event Data from 73 civil conflicts in Africa to estimate how changes in government and rebel tactical choices on where and when to fight battles affect expected utility estimates and, therefore, civil war outcomes.